Prediction of gene action content of Na, K, and Chlorophyll for Soybean Crop Adaptation to Salinity - Fachrina Wibowo; Armaniar Armaniar (Department of Crop Science, Faculty of Agriculture, Andalas University, 2019)
Salinity area experienced an expansion that is the caused contamination of irrigation water, seawater intrusion, drought stress and excessive uses of fertilizers.varieties is one of the plant breeding programs to resolve the salinity problem, before that, however, the breeder must know plant adaptation mechanisms in morphology, physiology and biochemical so that the plant can be categorized adapt and as having potential for the tolerant varieties. This writing aims to know the action of genes through skewness and kurtosis estimation pattern Na, K, and chlorophyll content, so it is known if plant-able to adapt with salinity. This research used a destructive analysis. (A) Anjasmoro varieties, (G) Grobogan varieties, (N) Grobogan varieties that have been through repeated selection as a comparison. Research result shows the tolerant varieties having high K + ions.